2018
DOI: 10.1111/myc.12849
|View full text |Cite
|
Sign up to set email alerts
|

Identification and biofilm development by a new fungal keratitis aetiologic agent

Abstract: We report the identification of a fungus, a member of the genus Neoscytalidium which is associated with human keratitis. Phylogenetic analysis and morphological observations on conidiogenous cells, which occur only in arthric chains in aerial mycelium and the coelomycetous synasexual morph is absent, identified a new species, Neoscytalidium oculus sp. nov. The fungus formed biofilm at a concentration of 1 × 10 conidia/mL, during 96 hours of incubation at 37°C, and also manifested haemolysis and melanin product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Recently, using sequencing of the ITS1+5.8S+ITS2 rDNA region, or of a fragment of the 28S large subunit ribosomal (LSU), it has been possible to recognize the species N. novaehollandiae , N. orchidaceous , N. dimidiatum , and N. oculus [3,11]. In the present study, the high level of accuracy of using the ITS1+5.8S+ITS2 rDNA region to identify N. dimidiatum reveals that this barcode is fit-for-propose in the clinical field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, using sequencing of the ITS1+5.8S+ITS2 rDNA region, or of a fragment of the 28S large subunit ribosomal (LSU), it has been possible to recognize the species N. novaehollandiae , N. orchidaceous , N. dimidiatum , and N. oculus [3,11]. In the present study, the high level of accuracy of using the ITS1+5.8S+ITS2 rDNA region to identify N. dimidiatum reveals that this barcode is fit-for-propose in the clinical field.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, within this genus, four species are recognized: N. novaehollandiae , N. orchidacearum , N. oculus , and N. dimidiatum [2,3]. The first two species have been reported as phytopathogens, while N. oculus and N. dimidiatum have been associated to ocular or keratinized tissue (skin or nails) infections, which are indistinguishable from dermatophytosis [3,4,5]. Recently, it has been demonstrated that N. oculus can form biofilms and cause hemolysis [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mexico, fungal keratitis is a poorly documented and understood problem, which is mainly studied in hospitals 1 . There are few reports regarding keratomycosis as health problem.…”
Section: Introductionmentioning
confidence: 99%